Magnetotactic bacteria from Pavilion Lake, British Columbia - Oestreicher, Zachery; Lower, Steven K.; Rees, Eric; Bazylinski, Dennis A.; Lower, Brian H. (Frontiers in Microbiology, 2013)
Pavilion Lake is a slightly alkaline, freshwater lake located in British Columbia, Canada (50o51’ N, 121o44’W). It is known for unusual organosedimentary structures, called microbialites that are found along the lake basin. These deposits are complex associations of fossilized microbial communities and detrital- or chemical-sedimentary rocks. During the summer, a sediment sample was collected from near the lake’s shore, approximately 25-50 cm below the water surface. Magnetotactic bacteria (MTB) were isolated from this sample using a simple magnetic enrichment protocol. The MTB isolated from Pavilion Lake belonged to the Alphaproteobacteria class as determined by nucleotide sequences of 16S rRNA genes. Transmission electron microscopy (TEM) revealed that the bacteria were spirillum-shaped and contained a single chain of cuboctahedral-shaped magnetite (Fe3O4) crystals that were approximately 40 nm in diameter. This discovery of MTB in Pavilion Lake offers an opportunity to better understand the diversity of MTB habitats, the geobiological function of MTB in unique freshwater ecosystems, and search for magnetofossils contained within the lake’s microbialites.